Strategi Menanggulangi Fenomena Geng di Kecamatan Semampir Wilayah Surabaya Utara - Karina Salma; M. Turhan Yani; M. Jacky (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The phenomenon of youth gangs in Semampir District, North Surabaya, has become a significant social issue that threatens public security, social order, and adolescent development. Gang involvement is influenced not only by individual factors but also by family dysfunction, peer influence, community environments, identity formation, and weak social control. These multidimensional causes require comprehensive intervention through collaborative efforts among multiple stakeholders. This study aims to analyze the strategies implemented by internal stakeholders, particularly educational institutions, and external stakeholders, including the district government, law enforcement agencies, community organizations, and local residents, in addressing the youth gang phenomenon in Semampir District, North Surabaya. This study employed a qualitative approach using an explanatory case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving school principals, teachers, parents, police officers, district government officials, community leaders, social organizations, as well as current and former gang members. The data were analyzed using Yin's case study analysis, which includes data organization, explanation building, narrative development, and conclusion drawing. Data credibility was ensured through source triangulation. The findings reveal that gang prevention and intervention strategies are implemented through preventive, pre-emptive, repressive, and rehabilitative approaches. Internal stakeholders emphasize character education, counseling services, parental involvement, student supervision, and digital literacy. Meanwhile, external stakeholders focus on community policing, law enforcement, cross-sector collaboration, youth empowerment programs, and community-based initiatives, such as Kampung Pancasila and Iwak Wader.